A influência da abundância populacional de adultos e/ou imaturos de uma trepadeira invasora, bem como da sua espécie suporte, na chuva de sementes - Oliveira, Ana Lívia de Castro Severo de (2023)
The study of the factors that influence the arrival of seeds in a locality, the seed rain, helps to understand the potential for regeneration and spatial expansion of plant populations. The seed rain is therefore critical to understanding and controlling the spread of invasive species, a threat to global biodiversity, economies and human health. Hence, we aimed to investigate which factors influence the seed rain of the invasive vine Cryptostegia madagascariensis Bojer. To this end, we collected the seed rain from three permanent monitoring sites in the years 2019 and 2020. This collected material was analyzed and the Cryptostegia madagascariensis seeds counted at the Vegetal Experimentation Laboratory of the Federal University of Ceará (UFC). In addition, we collected data on the abundance and population structure of the species C. madagascariensis and Copernicia prunifera (Mill.) H.E.Moore, a native palm frequently used by the invasive as a support. Data analyzes were carried out in the R computational environment using mixed generalized linear models (GLMM), in order to relate seed rain to the proposed predictive variables, including the year of collection as a random variable. Regarding the variables, they were divided into two scales: (i) regional, climatic differences between the three monitoring sites; and (ii) locations, abundance of individuals of the species C. madagascariensis and Copernicia prunifera. In total, we counted 938 seeds of the species C. madagascariensis. Caucaia being the most abundant site. The seed rain is influenced by the monitoring site, the abundance of adult individuals of the species C. madagascariensis and the additive effects between these two factors. The abundance of C. madagascariensis individuals negatively influenced seed rain. This effect varied according to the monitoring sites. The seed rain was not influenced by population abundance of C. prunifera or any additive relationship with this variable. To summarize, we found that seed rain is regulated by population density itself and that the environment in which the invasive population establishes itself is an important factor in determining its seed rain and potential density.